2006
DOI: 10.1002/j.2161-007x.2006.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Suffering: A Preliminary Study of Changes in Religious Women Adjusting to Severe Adversity

Abstract: This qualitative study examined interviews from 25 women who held theistic beliefs from Christian, Islamic, or Jewish traditions. All had recently experienced severe adversity but reported they were coping well. Analysis illustrated changes in religious beliefs and attitudes they made as a result of learning to cope. Differences were found among the 3 religious groups. Findings of this preliminary study suggest that religious meaning and experience may change because of the process of learning to cope with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…Patients who rely on spiritual beliefs are more likely to use an active coping style, and they seem to accept their illness in a positive and purposeful way [30]. Differently, there is an external-directing style when the events are perceived as out of individual's control.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients who rely on spiritual beliefs are more likely to use an active coping style, and they seem to accept their illness in a positive and purposeful way [30]. Differently, there is an external-directing style when the events are perceived as out of individual's control.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, these researches reported an association between spiritual well-being and a sense of hope among patients with cancer [18]. Individuals who experience the existential benefits of religious and/or spiritual perspective may also experience less distress after treatment [30]. In addition of physical burden of cancer, psychological distress including depression, anxiety, and feelings of hopelessness are common reactions in people with a cancer diagnosis, especially in the terminal phase of the illness [20].…”
Section: Introductionmentioning
confidence: 98%
“…The findings of these studies are also consistent with national figures reporting that a majority of the U.S. population believes in God or a Higher Power (Harris Interactive, Inc., 2006). In religious women dealing with adversity, there is also evidence that religious practices and spiritual beliefs develop and deepen during the process of coping with stressful experiences (Williams, Jerome, White, & Fisher, 2006). …”
mentioning
confidence: 99%
“…However, much of the local church work focuses on alleviation of suffering in the physical sense through donations of food, clothing and reduced fee medical care. The writings of the church urge believers to care for the sick and help the poor as their founder the Apostle Mark did so by assisting others in their suffering; focus is taken away from one's own suffering resulting in a modeling of Christ's behavior of service and humility (Shenouda, 1999;Williams, Jerome, White & Fisher, 2006).…”
Section: Copts and Sufferingmentioning
confidence: 99%
“…However, the interpretation and expectation of suffering is shaped by many factors. In the last decade, social scientists have focused on social-cultural aspects of suffering and have found that religious and personal beliefs change the perception of suffering and therefore the interpretation of suffering (Fulford, 2017; Tzounis, Kerenidi, Daniil, Hatzoglou, Kotrotsiou & Gourgoulianis, 2016; Kéri, 2015;Koenig, 2012;Balboni, Vanderwerker, Block, Paulk, Lathan, Peteet & Prigerson, 2007;Tarakeshwar, Vanderwerker, Paulk,Pearce, Kasl & Prigerson, 2006; Wilkinson, 2001;Williams, Jerome, White & Fisher, 2006;Gordon, Feldman, Crose, Schoen, Griffing & Shankar, 2002). The purpose of this paper is to examine the influence of religion and culture on the meaning of suffering in Zabbaleen women of Cairo, Egyptfrom a healthcare perspective in the context of having Hepatitis C. This community lives in a society that incorporates traditional Egyptian beliefs and strong Christian religion in a larger society of Islam.…”
mentioning
confidence: 99%